1996
DOI: 10.1055/s-2007-994319
|View full text |Cite
|
Sign up to set email alerts
|

Conflicts Between Physicians and Patients in Non-Elective Cesarean Delivery: Incidence and the Adequacy of Informed Consent

Abstract: A study was undertaken in 372 consecutive patients undergoing non-elective cesarean delivery to explore the incidence and nature of conflicts between physician and patient surrounding the decision to undergo non-elective cesarean delivery; to examine the adequacy of informed consent at the time of non-elective cesarean delivery; and to describe the importance of a preventive ethics approach to non-elective cesarean delivery. During a 6-month interval, all patients who underwent non-elective cesarean delivery a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…A number of studies have identified poor communication as a significant negative predictor of maternal satisfaction, [24,25] but none of them assessed to what extent it influenced satisfaction. Poor communication resulted in patientdoctor conflict in 8.3% of cases in one study, resulting in failure to give informed consent for delivery [26].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have identified poor communication as a significant negative predictor of maternal satisfaction, [24,25] but none of them assessed to what extent it influenced satisfaction. Poor communication resulted in patientdoctor conflict in 8.3% of cases in one study, resulting in failure to give informed consent for delivery [26].…”
Section: Discussionmentioning
confidence: 99%
“…The issue of informed consent for cesarean section has been addressed by several authors [7,38,44,45,46]. Most women interviewed after a non-emergency cesarean were satisfied with their surgery, felt that adequate prenatal and preoperative information was given, and understood the indication for their cesarean section [11,14,17,44].…”
Section: Discussionmentioning
confidence: 99%
“…Most women interviewed after a non-emergency cesarean were satisfied with their surgery, felt that adequate prenatal and preoperative information was given, and understood the indication for their cesarean section [11,14,17,44]. Patients were less likely to report informed consent when an emergency cesarean was necessary [14].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge there is not any law passed to force a pregnant woman to undergo invasive fetal treatment outside mainly historical legal orders of performing cesarean section for fetal distress (Lescale et al, 1996). Furthermore, as previously mentioned, embarking on fetal invasive therapy or surgery is a long-term commitment encompassing perinatal care, postnatal treatment and long-term follow-up, including medical and societal aspects, which cannot be successful without the full and active cooperation of the pregnant woman to begin with.…”
Section: Evidence-based Fetal Therapymentioning
confidence: 99%